2009
DOI: 10.1007/s10803-009-0806-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Behaviour: Is Social Anxiety Low in Williams Syndrome?

Abstract: Individuals with Williams syndrome (WS) exhibit striking social behaviour that may be indicative of abnormally low social anxiety. The present research aimed to determine whether social anxiety is unusually low in WS and to replicate previous findings of increased generalised anxiety in WS using both parent and self report.Fifteen individuals with WS aged 12-28 years completed the Spence Children's Anxiety Scale (SCAS) and the Children's Automatic Thoughts Scale (CATS). Their responses were compared to clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Similar prevalence rates have also been found in samples of adults with WS Dykens, 2003). Interestingly, however, there is little evidence that rates of Social Phobia are elevated in this population; prevalence rates and levels of anxiety symptoms tend to be consistent or lower than those reported in typically developing groups Dodd, Schniering & Porter, 2009;Leyfer et al, 2006).…”
Section: 1supporting
confidence: 66%
“…Similar prevalence rates have also been found in samples of adults with WS Dykens, 2003). Interestingly, however, there is little evidence that rates of Social Phobia are elevated in this population; prevalence rates and levels of anxiety symptoms tend to be consistent or lower than those reported in typically developing groups Dodd, Schniering & Porter, 2009;Leyfer et al, 2006).…”
Section: 1supporting
confidence: 66%
“…Often, it is assumed, for example, that individuals with WS are hypersociable, with atypically low levels of social anxiety. However, a recent report suggests that individuals with WS experience symptoms of social anxiety at the same level as mental age matched peers (Dodd et al, 2009). The HPA is especially responsive to socio-evaluative situations (Dickerson & Kemeny, 2004), rendering it a particularly promising way of sorting out reactivity to social versus non-social anxiety and stressors in WS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is possible that eye-gaze allocation to emotional facial expressions may be related to variation in levels of anxiety and social impairments in WS. In recent years, evidence has suggested that alongside increased sociability exists a strikingly opposing profile of increased non-social anxiety in WS ( Leyfer, Woodruff-Borden, Klein-Tasman, Fricke, & Mervis, 2006;Dodd, Schniering, & Porter, 2009). In particular, high levels of generalised anxiety disorder (GAD) as well as disorder specific fears and phobias have been identified in individuals with WS (Blomberg, Rosander, & Andersson, 2006;Rodgers, Riby, Janes, Conolly & McConachie , 2012).…”
mentioning
confidence: 99%